THE EFFECTIVENESS OF THE PROBLEM BASED LEARNING ON GRADE FIVE CRITICAL THINKING SKILLS - Setyowati, Setyowati (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2022)
This research aims to analyze the effect of applying the Problem Based Learning model on critical thinking skills in science in fifth grade elementary school students. This study uses a quasi-experimental method by comparing the treatment of the teaching and learning process in the experimental class and the control class. The research design used is the Non-equivalent Control Group Design. The population is all fifth grade students of public elementary schools in the Gunung Semeru cluster, Mijen District, Demak Regency. The sample in this study was taken from 2 elementary schools with a purpose sampling technique. The research instrument was 10 essay questions. Data analysis techniques in the form of instrument testing, prerequisite testing and hypothesis t. The result of the research is that there is a significant effect on the use of Problem Based Learning (PBL) models on critical thinking skills in science with t count of 23,318 while t table with 2, 0244 means 23.318 2, 0244, then Ho is rejected and Ha is accepted Suggestions on the importance of applying the Problem Based Learning model in the learning process because it is in accordance with education in the context of the 21st century. Where in education today students must be more responsive to changing times